The experimental testing of methodological system of integrated teaching of future academic Japanese philologists within master course - Asadchih, Oksana (ScienceRise: Pedagogical Education, 2017)
The research considers different aspects of the experimental probation of the methodological system of the integrated study of future philologists of Japanese academic speech within the master course. The criteria and parameters of the academic literacy formation within the master course were offered. For realization of the experimental verification of the effectiveness of the integrated system of Japanese academic speech teaching was chosen the classic three-stage experiment organization, according to which it is realized at the ascertaining, formation and control (statistic) stages. Each of them was introduced to the experiment program. As a result of the experiment were confirmed the theoretical grounds of the conception of the integrated system of Japanese academic speech teaching according to the content criteria. It was proved that practical results and recommendations are actual, essential and still be unpublished according to the results of other didactic studies. As a result of the experiment: results of the methodological system introduction into the educational process were described and evaluated, conditions of the experimental results were characterized, data about participants, means and methods of the experiment were presented; limits of the experimental method use were outlined